PROSES SUKSESI KEPEMIMPINAN PADA PERUSAHAAN KELUARGA (STUDI PADA HOTEL SRI INDRAYANI PEKANBARU) - Naldi, Syafri; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Leadership succession is about leadership transition. The transition is fundamental in business or corporation, moreover at family business because it is potential to bring about conflict and disunity. When it happened, certainly business sustainability will be disturbed, even the business could get lose ground. Finally, only few businesses can survive until third generation and forth. Business success and sustainability will be guaranted by mature leadership succession planning. This research is done to get understanding about succession of leadership, especially at Sri Indrayani’s Hotel.The research used qualitative method to find depth understanding of leadership succession process. To get data, the researcher used interview, observation, and study literature as complementary. The data has been analyzed with some theories like succession, leadership, and organization culture.Result of analysis showed the previous leader struggled to transfer leadership values, skills, and knowledge to successor candidates. Leadership succession process which has been done including preparation like support for formal study, training, and working outside the corporation for candidates. The next, involving candidates in the business like controlling and supervising employees, and also involves in business general meeting. The last, implementation of succession itself. Keywords: Succession, Leadership, Business